Understanding Shared Services in SAP S/4HANA AMS: Insights from Indian IT Service Providers Through a Mixed Methods Study - Pillai, Sunil Sasidharan (Digital Repository of Theses, 2025)
This study explores the shared services model within SAP S/4HANA Application Management Services (AMS), focusing on Indian IT service providers. Leveraging a mixed-methods approach, the research integrates qualitative insights from semi-structured interviews and focus groups with quantitative data from a structured survey. The research objectives include understanding shared services in SAP AMS, examining factors influencing productivity and efficiency and exploring the impact of emerging technologies on shared services models. The study identifies eight themes in a bid to articulate the shared services model as being practiced in SAP AMS. Key findings highlight the transformation of shared services from cost-centric models to strategic enablers aided by customer, geographic and organisational maturity. Twelve themes emerge as significant influencers of productivity, including workload balancing, knowledge accessibility, supportive leadership, and AI-driven ITSM tools. Quantitative data corroborates the qualitative insights, revealing trends in workload distribution, consultant preferences, and the impact of mentorship and recognition programs. The study also uncovers nine themes shaping the future of SAP AMS, emphasizing the transformative role of AI in redefining shared services, enabling predictive insights and personalized support. However, it necessitates the evolution of workforce skills and triggers the emergence of hybrid roles, and automation-resilient skills. This research contributes to the theoretical and practical understanding of shared services in SAP AMS by offering actionable recommendations for practitioners. The findings aim to guide IT leaders in optimizing shared services for scalability, efficiency, and alignment with emerging trends.